Validation of the Portuguese version of impulsive-premeditated aggression scale in an inmate population - Azevedo, JC (2018)
Aggression is one of the core symptoms of antisocial personality disorder (ASPD) with therapeutic and prognostic relevance. ASPD is highly prevalent among inmates, being responsible for adverse events and elevated direct and indirect economic costs for the criminal justice system. The Impulsive/Premeditated Aggression Scale (IPAS) is a self-report instrument that characterizes aggression as either predominately impulsive or premeditated. This study aims to determine the validity and reliability of the IPAS in a sample of Portuguese inmates. A total of 240 inmates were included in the study. A principal component factor analysis was performed so as to obtain the construct validity of the IPAS impulsive aggression (IA) and premeditated aggression (PM) subscales; internal consistency was determined by Cronbach's alpha coefficient; convergent and divergent validity of the subscales were determined analyzing correlations with the Barratt Impulsiveness scale, 11th version (BIS-11), and the Psychopathic Checklist Revised (PCL-R). The rotated matrix with two factors accounted for 49.9% of total variance. IA subscale had 11 items and PM subscale had 10 items. The IA and PM subscales had a good Cronbach's alpha values of 0.89 and 0.88, respectively. The IA subscale is correlated with BIS-11 attentional, motor, and non-planning impulsiveness dimensions (p < 0.05). The PM subscale is correlated with BIS-11 attentional, motor impulsiveness dimensions (p < 0.05). The PM subscale is correlated with PCL-R interpersonal, lifestyle, and antisocial dimensions (p < 0.05). The IA subscale is not correlated with PCL-R. The Portuguese translated version of IPAS has adequate psychometric properties, allowing the measurement of impulsive and premeditated dimensions of aggression.